FACTORS AFFECTING THE QUALITY OF THE PERFORMANCE ACCOUNTABILITY REPORT OF GOVERNMENT AGENCY WITH ORGANIZATIONAL COMMITMENTS AS A MODERATING VARIABLE WHITIN TECHNICAL IMPLEMENTATION UNITS OF DIRECTORATE GENERAL OF EARLY CHILDHOOD EDUCATION AND COMMUNITY ED - Zahro, Fatimah Harahap (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to analyze the influence of the clarity of budget target, the competence of human resources, and the effectiveness of internal audit simultaneously and partially on the quality of LAKIP (The Performance Accountability Report of Government Agency) within the UPT Ditjen PAUD Dikmas (Technical Implementation Unit of Directorate General of the Early Childhood Education and Community  Education) with Organizational Commitment as moderating variable. The research used associative qualitative method. The population was 8 PPKs (Commitment Officers), 24 SPIs (Internal Supervising Units), 8 Section Heads of Program Development, 8 Budget Organizers, and 8 LAKIP Organizers in the Technical Implementation Units at the Ditjen PAUD Dikmas, and all of them were used as the samples (56 samples). Primary data were analyzed by using multiple linear regression analysis and residual test. The result of the research showed that the clarity of budget target, the competence of human resources, and the effectiveness of internal audit simultaneously and partially had significant influence on the quality of LAKIP. Organizational Commitment was able to moderate the correlation of the clarity of budget target and the competence of human resources with the quality of LAKIP whitin the UPT Ditjen PAUD Dikmas, but it was not able to moderate the correlation between the effectiveness of internal audit and the quality of LAKIP whitin the UPT Ditjen PAUD Dikmas.